An efficient LC-MS method for isomer separation and detection of sugars, phosphorylated sugars, and organic acids - Koley, Somnath (Journal of experimental botany, 2022)
© Natural Resources Canada 2022. Published by Oxford University Press on behalf of the Society for Experimental Biology.